#50: Cytomegalovirus Retinitis Among Pediatric Hematopoietic Stem Cell and Solid Organ Transplantation Recipients: A Contemporary Review. (28th June 2021) - Cruz-Vidal, D A; Sayegh, R; Ouellette, C; Song, E; Ardura, M I
Abstract: Background: Cytomegalovirus infection can cause significant morbidity and mortality after transplantation. Cytomegalovirus retinitis (CMVR) can be a major complication of tissue invasive CMV disease in transplant recipients. There are little data regarding the contemporary incidence and outcomes of CMVR among pediatric transplant recipients. Methods: We performed a retrospective cohort analysis of allogeneic hematopoietic (allo-HCT) and solid organ transplant (SOT) recipients who received medical care at Nationwide Children's Hospital (NCH) from 1/1/10–11/30/20 and had a diagnosis of CMVR to describe the incidence, timing post-transplant, ocular manifestations, management, and outcomes. Basic demographic and clinical data, pre-transplant donor/recipient CMV serostatus, and post-transplant CMV infection data were collected. Graft-specific CMV surveillance and prophylaxis strategies were performed according to NCH hospital guidelines. During the study period, quantitative plasma CMV PCR assays included copies/mL (2010–2013) and WHO international standard IU/mL (2013–2020). Results: During the 10-year study period, 347 patients underwent allo-HCT (N=214) or SOT (N=133; heart N=46, liver N=36, kidney N= 52; 1 patient had concomitant kidney and liver transplantation); median age was 8.6 years [range 0.1–25.9] and 198 (56.5%) were male. In total, 98 patients had CMV DNAemia post-transplant, and CMVR was diagnosed in 3 (HCT=2, SOT=1), for an overall CMVR incidence of 0.86% among all transplant recipients and occurring in 3% of patients with CMV DNAemia. No CMVR was diagnosed in patients without CMV DNAemia. An ophthalmologic examination was performed in 58 (59%) of patients with any DNAemia compared with 67 (27%) of patients without DNAemia. CMVR was diagnosed on funduscopic examination a median of 183 days [range 34–512] post-transplant based on visual symptomatology (N=2) or by routine eye screening prompted by DNAemia (N=1). CMV DNAemia at the time of CMVR was 1, 463 copies/mL, 3, 000, and 14, 204 IU/mL; all patients had prolonged (>3 months) CMV detection before CMVR. One SOT recipient had concomitant pathology confirming CMV gastrointestinal tract disease. Two of the 3 CMVR cases occurred in the setting of genotypic UL94 CMV resistance mutations (A594V, H520Q)(Figure 1). Two patients were already receiving CMV antiviral therapy (maribavir N=1; valganciclovir=1) at the time of CMVR diagnosis. After the CMVR diagnosis, all patients were prescribed systemic foscarnet. Adjunctive therapies included concurrent intravitreal antiviral therapy (ganciclovir N=1; foscarnet N=1) and adoptive immunotherapy with CMV antiviral specific T-cells (N=1, HCT). Improvement of ocular symptoms occurred in 2 patients at 15 and 20 days after starting targeted CMV antiviral therapy; one patient developed permanently impaired vision. Conclusion: CMVR remains as an important complication in transplant recipients. Although CMVR incidence was low in our cohort of transplant recipients, it occurred most frequently in cases of CMV resistance, prolonged DNAemia, and led to permanent visual impairment in 1 of 3 patients. The development of resistant CMV may have a role in the occurrence, progression, and severity of CMVR. Additional pediatric-specific data are needed to better characterize CMVR and inform optimal prevention strategies.